Against interpretation : and other essays - Sontag, Susan (New York : Picador, 2001)
Against Interpretation was Susan Sontag's first collection of essays and is a modern classic. Originally published in 1966, it has never gone out of print and has influenced generations of readers all over the world. It includes the famous essays "Notes on Camp" and "Against Interpretation," as well as her impassioned discussions of Sartre, Camus, Simone Weil, Godard, Beckett, Levi-Strauss, sceince-fiction movies, psychoanalysis, and contemporary religious thought.
Bibliografske bilješke uz tekst
Keywords: književnost - interpretacija; povijest; književna kritika